Assessing Planting Date Effect on Soybean Yield and Dry Down for Different Maturity Groups and Planting Dates in Eastern Kansas - Tainá H. da Silva; Venicius E. Pretto; Gabriel da R. Hintz; Eric Adee; Ignacio A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
The United States (US) ranks as the second-largest global soybean producer. Especially in Kansas, soybean relevance relates to the double-cropped soybean after winter wheat. While this cropping system allows efficient land use, late planting dates may reduce soybean yields. For this reason, understanding the impact of planting dates on yield is crucial for Kansans farming. Our goals were to: 1) explore the interaction between planting date and soybean maturity group (MG); and 2) characterize the soybean seed filling and dry down processes in Kansas. An experiment was carried out in Topeka, under irrigation during the 2023 growing season. Five genotypes and two planting dates (early and late) were tested. Our results showed that delaying the planting date increased moisture lost per growing degrees days (GDD). Furthermore, late planting date requires less GDD than an early planting date, resulting in a faster dry down, affecting the dry down process. Furthermore, our study showed significant impact of MG for both planting date on seed yield. The highest yields were achieved by MGs 3.4, 3.8, and 4.2, regardless of the planting dates, averaging 84, 81, and 90 bu/a for the early dates, and 80, 77, and 80 bu/a for late planting dates. The shortest and the longest MGs (2.8 and 5.2) presented yield penalties.
Keywords: dry down; planting date; double crop; maturity groups